How Do Consumers Adapt to a New Environment in their economic forecasting? Evidence from the German Reunification. - Olga Goldfayn-Frank; Johannes Wohlfart (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Exploiting the natural experiment of the German reunification, we examine how consumers adapt to a new environment in their macroeconomic forecasting. We document that East Germans expect higher inflation and make larger forecast errors than West Germans even decades after reunification. Differences in consumption baskets, financial literacy, risk aversion or trust in the central bank cannot fully account for these patterns. We find most support for the explanation that East Germans, who were used to a strong norm of zero inflation, persistently overadjusted the level of their expectations in the face of the initial inflation shock in reunified Germany. Our findings suggest that large changes in the economic environment can permanently impede people's ability to form accurate macroeconomic expectations, with an important role for the interaction of old norms and new experiences around the event.
Keywords: D12; D14; D83; D84; G11; 330; Expectation Formation; Inflation; Natural Experiment; German Reunification; Macroeconomic Experiences